A digital strategy for Europe - Bruno Maç\~aes (European Centre for International Political Economy (ECIPE), 2015)
The industrial internet - the network of intelligent machines, software analytics and people - would address the European productivity slowdown by providing a foundation for new businesses, new jobs and higher productivity. While the new Digital Single Market (DSM) strategy makes a number of valuable contributions, it is predominantly focused on the consumer side of the digital economy. But this paradigm has now been substantially exhausted. We need to fundamentally change internet growth from the consumer side to the widespread digitalisation of industry. On this, the new strategy falls short and may be in need of some future development and revision. This is in some way a missed opportunity to further connect the DSM with the EU's agenda of structural reform, with a renewed emphasis on employment, growth and productivity. (...)
Keywords: 330; EU-Binnenmarkt; E-Business; Industrie 4.0; EU-Staaten